2016
DOI: 10.4208/cicp.060515.161115a
|View full text |Cite
|
Sign up to set email alerts
|

A Computational Study of a Data Assimilation Algorithm for the Two-dimensional Navier-Stokes Equations

Abstract: We study the numerical performance of a continuous data assimilation (downscaling) algorithm, based on ideas from feedback control theory, in the context of the two-dimensional incompressible Navier-Stokes equations. Our model problem is to recover an unknown reference solution, asymptotically in time, by using continuous-in-time coarse-mesh nodal-point observational measurements of the velocity field of this reference solution (subsampling), as might be measured by an array of weather vane anemometers. Our ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 19 publications
5
86
0
Order By: Relevance
“…In the previous sections, we showed that the data assimilation algorithm (2.13) can still perform well even when there is error in the viscosity parameter, provided that µ is large and h is small. However, for large values of the Grashof number satisfying the requirements of the rigorous estimates would require prohibitively small values of h. Fortunately, in practice the requirements on h and µ need not be strict when Re 1 is known, and in fact we would expect the algorithm to perform well with very modest values for h and µ (see [31]).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…In the previous sections, we showed that the data assimilation algorithm (2.13) can still perform well even when there is error in the viscosity parameter, provided that µ is large and h is small. However, for large values of the Grashof number satisfying the requirements of the rigorous estimates would require prohibitively small values of h. Fortunately, in practice the requirements on h and µ need not be strict when Re 1 is known, and in fact we would expect the algorithm to perform well with very modest values for h and µ (see [31]).…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Moreover, the algorithm may continue to work with values of h much larger and values of λ much smaller than required by our analysis. For example, computational experiments performed by [16] for a different spatially filtered continuous data assimilation method based on nudging show that the method performs far better than the analytical estimates suggest. We conjecture similar numerical effectiveness for the discrete data assimilation method described in the present paper.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding related numerical studies, [GOT16] demonstrated in the case of the 2D NSE that the number of observables required for synchronization using (1.2) is much lower in practice than what has been deemed sufficient by the rigorous analysis. In the setting of the 2D RB system, numerical studies were carried out in [ATG + 17], and then in [FJJT18] for nearly turbulent flows using vorticity and local circulation measurements.…”
Section: Introductionmentioning
confidence: 99%